Growth of crystalline semiconductor structures on amorphous substrates for photovoltaic applications. Issue 1 (10th January 2017) - Boeck, T.; Ringleb, F.; Bansen, R.
Abstract : The growth of defined crystalline structures on amorphous materials is an almost generally difficult task. Due to the lack of a crystallographic lattice, no epitaxial intergrowth can be realized. However, for many applications the growth of crystalline layers or microstructures on such substrates is required. For large area devices such as solar cells, locally selective seeding of silicon or chalcopyrite on glass is a promising method. Abstract : The growth of defined crystalline structures on amorphous materials is an almost generally difficult task. Due to the lack of a crystallographic lattice, no epitaxial intergrowth can be realized. However, for many applications the growth of crystalline layers or microstructures on such substrates, or on amorphous or nanocrystalline intermediate layers is required. For large area applications such as solar cells, glass is a particularly favored material. The article presents two studies from the field of photovoltaics. Both are characterized by a locally selective seeding: the growth of crystalline Si on glass by steady‐state solution growth on a partially crystallized Si seed layer, and the preparation of CuInSe2 absorber islands for micro concentrator solar cells from spatially confined metallic indium droplets.